Can the Stock Market Predict M&A Success? A Comparison between the US and Asian Emerging Markets. - Ngo, Nguyen Dong Ha (2015)
In the past few years, mergers and acquisitions (M&A) have reached their new records in terms of volume as well as value and become a preferable investment strategy of companies in over the world. An extensive number of empirical researches have been conducted to examine the impact of M&A on firm performance in both the short run and long run; however, the findings are inconclusive. Most of them have employed only one measure of the M&A performance, either the event study or the accounting-based approach, which is believed to be unable to fully reflect all aspects of the M&A influence. For this reason, our study uses both the event study to investigate the short-run impact of the M&A announcement on stock price performance and the accounting-based method to investigate the long-run impact of M&A on acquiring firms’ operating performance, and then further investigate whether the stock market reactions to the M&A announcement anticipate subsequent operating performance. Particularly, we examine at the same time two different samples, one includes 97 domestic M&A deals undertaken in the US and another one includes 77 domestic M&A deals undertaken in six Asian emerging countries, in order to verify whether the relation between announcement abnormal returns and operating returns is sensitive to the choice of markets with different levels of efficiency. The results suggest that the M&A announcement deteriorates the wealth of shareholders in the US market but improves the wealth of shareholders in emerging countries. In the long run, it brings value creation to acquiring firms in both markets. However, we find evidence of a zero relation between announcement abnormal returns and operating performance for US acquiring firms and a negative relation for Asian emerging firms. Managers of acquiring firms, therefore, should not rely on the stock market reactions to the M&A announcement to infer prospective operating performance since they might not present or even lead to misleading anticipation of economic gains or losses to acquiring firms in the future.